Finding the Key Players in Online Child Exploitation Networks - Bouchard, Martin (Policy & internet, 2011)
The growth of the Internet has been paralleled with a similar growth in online child exploitation. Since completely shutting down child exploitation websites is difficult (or arguably impossible), the goal must be to find the most efficient way of identifying the key targets and then to apprehend them. Traditionally, online investigations have been manual and centered on images. However, we argue that target prioritization needs to take more than just images into consideration, and that the investigating process needs to become more systematic. Drawing from a web crawler we specifically designed for extracting child exploitation website networks, this study 1) examines the structure of ten child exploitation networks and compares it to a control group of sports-related websites, and 2) provides a measure (network capital) that allows for identifying the most important targets for law enforcement purposes among our sample of websites. Results show that network capital — a combination between severity of content (images, videos, and text) and connectivity (links to other websites) — is a more reliable measure of target prioritization than more traditional measures of network centrality taken alone. Policy implications are discussed